2011
DOI: 10.3892/etm.2011.325
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of ovarian large-cell neuroendocrine carcinoma: Four case reports and review of the literature

Abstract: Abstract. The objective of the present study was to present 4 recently encountered ovarian large-cell neuroendocrine carcinoma (LCNEC) cases, and to evaluate their clinicopathological features in the context of the previously reported 29 LCNEC cases. First, we described the clinical features of 4 recently encountered cases. Routine H&E staining and immunohistochemistry for CD56, synaptophysin and chromogranin A were performed on sections of both the LCNEC and epithelial carcinoma components. Clinical data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…There were no significant differences between the cases with FIGO stage I/II (n = 28) and III/IV (n = 25), with total 5-year survival of 38.8 and 29.2% and median survival time of 19 and 9 months, respectively (p = 0.458). These results were almost similar to the previous report by Oshita et al [18], suggesting that cases with LCNEC showed much worse clinical outcomes than the other subtypes, such as epithelial ovarian cancer even in early disease, regardless of FIGO stage. In particular, cases with carcinomatous peritonitis (n = 11) showed significantly much poorer clinical outcomes than cases without carcinomatous peritonitis (n = 42), with median survival time of 7 and 20 months, respectively (p = 0.036), suggesting that a different therapeutic strategy should be considered in these cases ( Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There were no significant differences between the cases with FIGO stage I/II (n = 28) and III/IV (n = 25), with total 5-year survival of 38.8 and 29.2% and median survival time of 19 and 9 months, respectively (p = 0.458). These results were almost similar to the previous report by Oshita et al [18], suggesting that cases with LCNEC showed much worse clinical outcomes than the other subtypes, such as epithelial ovarian cancer even in early disease, regardless of FIGO stage. In particular, cases with carcinomatous peritonitis (n = 11) showed significantly much poorer clinical outcomes than cases without carcinomatous peritonitis (n = 42), with median survival time of 7 and 20 months, respectively (p = 0.036), suggesting that a different therapeutic strategy should be considered in these cases ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The clinicopathological features of 31 cases with FIGO stage I/II (Table 1) and 25 cases with FIGO stage III/IV (Table 2) [7,8,14,17,18,20,[25][26][27][28][29][30][31][32][33][34][35] were reviewed. A Kaplan-Meier survival curve (SPSS Statistics version 24; IBM, Armonk, NY) of all 53 cases excluding 3 cases without clinical outcome data showed total 5year survival of 34.6% and median survival time of 17 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extremely rare clinical presentation of a huge mass arising from an anatomically normal ovary confirmed laparoscopically, 9 months back was reiterating the fact that this tumour was rapidly growing. Some authors have similar opinion [1][2][3][4][5][6].…”
Section: Discussionmentioning
confidence: 82%
“…This extremely rare clinical presentation of a huge mass arising from an anatomically normal ovary confirmed laparoscopically, 9 months back was reiterating the fact that this tumour was rapidly growing. Some authors have similar opinion [1–6]. …”
Section: Discussionmentioning
confidence: 90%